2007
DOI: 10.1097/mcg.0b013e31802c2a23
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Open-label Trial of Remicade® in Patients With Severe Exacerbation of Crohn's Disease Requiring Hospitalization

Abstract: IFX therapy was an effective first-line agent in patients with severe Crohn's disease who require hospitalization and therefore a primary treatment option. Most patients receiving IFX can anticipate a briefer hospitalization than with IV hydrocortisone. Failure of an early response can provide an opportunity to consider an alternate form of therapy sooner with IFX than with hydrocortisone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In this regard, our case series provides complementary data to the earlier work of Bhatia et al, which demonstrated the effectiveness of first-line treatment with IFX for patients with hospitalized CD but without prior failure of inpatient CS. 11 Bhatia's study, relying on the use of historical controls of inpatient CS response from Chun et al, demonstrated that initial hospital treatment with IFX was comparable to initial treatment with CS. 13 It is worth noting that Chun's study reported an almost 90% response to inpatient CS rescue with either IV adrenocorticotropic hormone or hydrocortisone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, our case series provides complementary data to the earlier work of Bhatia et al, which demonstrated the effectiveness of first-line treatment with IFX for patients with hospitalized CD but without prior failure of inpatient CS. 11 Bhatia's study, relying on the use of historical controls of inpatient CS response from Chun et al, demonstrated that initial hospital treatment with IFX was comparable to initial treatment with CS. 13 It is worth noting that Chun's study reported an almost 90% response to inpatient CS rescue with either IV adrenocorticotropic hormone or hydrocortisone.…”
Section: Discussionmentioning
confidence: 99%
“…The study showed that IFX therapy was an effective therapy as a first-line agent, but did not include patients already failing standard first-line treatment with intravenous CS. 11…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For patients with severe Crohn's symptoms requiring hospitalization, intravenous steroids are commonly prescribed, and a therapeutic effect is expected within 10 days (30). In an openlabel study (31), infliximab use was associated with a reduction in mean hospital stay by three days compared with patients treated with intravenous hydrocortisone. The use of TNF antagonist drugs in hospitalized patients should only be considered after sepsis has been excluded.…”
Section: Discussion Of Statementmentioning
confidence: 99%